Percentage of Live Coral Cover in The Regional Water Conservation Area of the Sawo “ Lahewa Water Tourism Park, North Nias District - Siregar, Zufriwandi; Barus, Ternala Alexander; Aththorick, T Alief (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2024)
Coral reefs are vital ecosystems facing serious threats due to climate change and human activities. This research aims to evaluate the condition of live coral cover in the Sawo-Lahewa Aquatic Tourism Park (TWP) Regional Marine Conservation Area (KKPD), North Nias Regency, as an important step in conservation and sustainable management efforts. Data was collected at 8 research stations using the Underwater Photo Transect (UPT) method. The research results show that the condition of coral reefs in this area is in the damaged to moderate category, with the percentage of live coral cover ranging between 12.33-45.37% and an average of 26.65%. The highest percentage of coral cover was found on Sarangbaung Island (45.37%) in the medium category, followed by Makora Island (42.13%), Gita Island (35.35%), and Lafau Island (31.07%). Meanwhile, locations with the lowest cover in the damaged category include Gosobaohi_01 Island (18.25%), Gosobaohi_02 Island (15.60%), Sifahandro Sea Waters (13.13%), and Bengkuang Bay Waters (12.33%). This research also looks at the abundance of coral juveniles, coral fish, and megabenthos to provide a broad picture of the health of the coral reef ecosystem. The results of this research can become a scientific basis for developing more effective management strategies. Apart from that, it is also a form of supporting conservation efforts, helping restore damaged ecosystems, and increasing the resilience of coral reefs to future environmental threats.Keywords: Coral Reefs, Regional Marine Conservation Area, North Nias